Bahasa Inggris - Ari Isnu Wibowo; Sularni; Merri Sri Hartati; Apriza Fitriani (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
Students go to school only as a daily routine with their friends so that education at school is not carried out optimally. Students carry out positive culture not because of their own desires (intrinsic motivation) but because they are afraid of being punished by the teacher. By trying to carry out community service implementing positive culture at SMPN 15 Bengkulu Utara, it is hoped that there will be a change in mindset and motivation for both educators and students. The results of the evaluation of community service activities regarding the implementation of positive culture show that the intrinsic motivation of school residents, namely around 80% of school residents, is enthusiastic about implementing positive culture so that the learning climate becomes more conducive